Crystallization of the chaperone protein SecB. - Vrielink, A. (Cold Spring Harbor Laboratory Press, 1995)
The secretory protein SecB found in Escherichia coli is a molecular chaperone that binds to precursor forms of a number of proteins targeted for export to the periplasmic space. SecB maintains these proteins in a translocation-competent conformation facilitating the translocation process. The material has been cloned and expressed in E. coli. Crystals have been grown from polyethylene glycol 8000 by vapor diffusion using the hanging drop technique. These crystals are monoclinic, belonging to space group C2 with unit cell dimensions a = 56.0 A, b = 111.1 A, c = 134.7 A, and beta = 104 degrees. The crystals diffract to 8 A resolution on a Rigaku imaging plate detector. Dynamic light scattering experiments suggest that SecB exhibits aggregation behavior with a number of different precipitating agents. These results may explain resistance of SecB to forming ordered crystals.